International news in the aspect of cross-border information and propaganda: the systemic determinants (Herald of Journalism, 2018)
The modern media field is increasingly seen as a platform for cross-border information and propaganda. The concept of international news is integrated into a number of related areas, which include international relations, foreign business interests, information security and security, more specifically, the viability and real independence of the state. Foreign information and international news act as part of a large flow, but part of the most dynamic, operational, constantly present in the information environment.ISSN 1563-0242 Herald of journalism. №2 (48). 2018 39ДудиновaЕ.И., Мухaмaдиевa Л.И.And, therefore, the most influential. This area forms the public opinion and are able to change it out ofnecessity and the wishes of a specific customer.The purpose of the article is to present a brief analysis of the international discourse of foreign news inthe format of systemic determinants of information and propaganda. The authors studied the internationalexperience of legislative regulation and control of news flows between States or international blocs. Kazakhstan’slaws in the field of international exchanges of mass information were also considered.The study of the content of foreign news of domestic and foreign news agencies for the period fromNovember 2017 to March 2018 has led to the following results: on average, 35% of the total materialof news portals in Kazakhstan are foreign news. The audience of consumers of foreign news to a greaterextent-young people under 35 years. Among them, more than 84% receive information through mobileapplications. The study also examines the factors of “soft power” for the impact of international news onthe formation of public opinion, the growth or decline in the political status and reputation of States, parties,specific leaders. The aspects of manipulation by means of feeding, frequency, selection and layoutof international news in the media of Kazakhstan are studied.The study of a number of parameters and indices of foreign news development confirmed the undoubtedinvolvement of this factor in the economic and political structure of the world media business.Key words: international news, “soft power”, propaganda, information security, information threat,media business.